POTENSI WISATA BUDAYA JALUR GULA DALAM MENUNJANG KENAIKAN KUNJUNGAN TAMU HOTEL DI KOTA SEMARANG - Syaiful Ade Septemuryantoro (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2017)
‘Jalur Gula’ culture is one of tourist destinations in Semarang city. The existence of ‘Jalur Gula,’ culture cannot be separated from the role of a person named Oei Tiong Ham, the king of sugar in Southeast Asia. This culture is located in the old area of Semarang city. This area used to be the center of trade and industry during the Dutch colonialization.This culture is expected to give the real contribution to the tourism sector in Semarang city. This study is aimed at describing the potency of ‘Jalur Gula’ cultural tourism in increasing the hotel occupation in Semarang city. To get this data, observation and library research were conducted. The result showed that ‘Jalur Gula’ culture has the high potency in increasing the hotel occupation in Semarang city. Since Semarang city is a part of sugar trade in the world, there are many tourists visiting Semarang city. When the number of tourist increases, it will also increase the hotel occupation in Semarang city. Keywords: cultural tourism, king of sugar, ‘Jalur Gula’ culture, hotel occupation in Semarang.